Railway transportation systems : design, construction and operation - Pyrgidis, Christos N. (Boca Raton, FL : CRC Press, 2022)
"This comprehensive overview covers the entire range of railway passenger systems, from conventional and high-speed intercity systems to suburban, regional, operating on steep gradients, and urban ones. New material provides innovations in rail freight transportation, case studies, and an update of cutting-edge technologies"--
The railway as a transport system -- Loads on track -- Behaviour of rolling stock on track -- Tramway -- Metro -- Monorail -- Automatic passenger transport railway systems of low- and medium- transport capacity -- Suburban railway -- Rack railway -- Cable railway systems for steep gradients -- Organisation and management of passenger intercity railway transport -- High-speed networks and trains -- Tilting trains -- Metric track gauge intercity railway networks -- Organisation and management of freight railway transport -- Heavy haul rail transport -- Operation of railway systems under specific weather conditions and natural phenomena -- Railway safety -- Railway and the natural environment -- The research in the railway domain : cutting-edge technologies in railways -- Applicability verification : a supporting tool for the conduction of feasibility studies of urban mass railway transportation systems.
Includes bibliographical references and index.
Keywords: Railroads -- Design and construction; Railroad engineering; Transportation engineering; Railroads; Chemins de fer -- Conception et construction; Chemins de fer; Transport -- Technologie; Railroads (infrastructure); Railroad engineering; Railroads -- Design and construction; Transportation engineering